Nanomedicines: A Potential Treatment for Blood Disorder Diseases - Zhang, Nan; Wei, Ming-Yuan; Ma, Qiang (Frontiers in Bioengineering and Biotechnology, 2019)
Blood disorder diseases (BDDs), also known as hematologic, is one of the diseases owing to hematopoietic system disorder. Chemotherapy, bone marrow transplantation, and stem cells therapy have been used to treat BDDs. However, the cure rates are still low due to the availability of the right type of bone marrow and the likelihood of recurrence and infection. With the rapid development of nanotechnology in the field of biomedicine, artificial blood or blood substitute has shown promising features for the emergency treatment of BDDs. Herein, we surveyed recent advances in the development of artificial blood components: gas carrier components (erythrocyte substitutes), immune response components (white blood cell substitutes), and hemostasis-responsive components (platelet substitutes). Platelet-inspired nanomedicines for cancer treatment were also discussed. The challenges and prospects of these treatment options in future nanomedicine development are discussed.